Composition of abyssal macrofauna along the Vema Fracture Zone and the hadal Puerto Rico Trench, northern tropical Atlantic. (February 2018) - Brandt, A.; Frutos, I.; Bober, S.; Brix, S.; Brenke, N.; Guggolz, T.; Heitland, N.; Malyutina, M.; Minzlaff, U.; Riehl, T.; Schwabe, E.; Zinkann, A.-C.; et al.
Abstract: We analyzed composition and variations in benthic macrofaunal communities along a transect of the entire length of the Vema-Fracture Zone on board of RV Sonne (SO-237) between December 2014 and January 2015 in order to test whether the Mid-Atlantic Ridge serves as a barrier limiting benthic taxon distribution in the abyssal basins on both sides of the ridge or whether the fracture zone permits the migration of species between the western and eastern abyssal Atlantic basins. The Puerto Rico Trench, much deeper than the surrounding abyssal West Atlantic, was sampled to determine whether the biodiversity of its hadal macrofauna differs from that of the abyssal Atlantic. The composition of the macrofauna from the epibenthic sledge catches yielded a total of 21, 332 invertebrates. Crustacea occurred most frequently (59%) with 12, 538 individuals followed by Annelida (mostly Polychaeta) (26%) with 5491 individuals, Mollusca (7%) with 1458 individuals, Echinodermata (4%) with 778 individuals, Nematoda (2%) with 502 individuals and Chaetognatha (1%) with 152 and Porifera (1%) with 131 individuals. All other taxa occurred with overall less than ten individuals (Hemichordata, Phoronida, Priapulida, Brachiopoda, invertebrate Chordata, Echiurida, Foraminifera (here refereed to macrofaunal Komokiacea only), Chelicerata, Platyhelminthes). Within the Crustacea, Peracarida (62.6%) with 7848 individuals and Copepoda (36.1%) with 44, 526 individuals were the most abundant taxa. Along the abyssal Vema-Fracture Zone macrofaunal abundances (ind./1000 m 2 ) were generally higher on the eastern side, while the highest normalized abundance value was reported in the Puerto Rico Trench at abyssal station 14-1 2313 individuals/1000 m 2 . The lowest abundance was reported at station 11-4 with 120 ind./1000 m 2 located at the western side of the Vema-Fracture Zone. The number of major macrofaunal taxa (phylum, class) ranged between five (stations 12-5, 13-4 and 13-5 at hadal depths in the Puerto Rico Trench) and 14 (station 9-8) in the western abyssal basin of the Vema-Fracture Zone. Differences are seen in the distribution of Porifera at macrofaunal level between eastern and western sides of the Vema-Fracture Zone. Macrofaunal composition of the study area is compared with data from other expeditions in the Atlantic and the northwest Pacific Ocean.